2021
DOI: 10.47391/jpma.952
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and impact of individual symptoms on quality of life in dry eye disease in patients presenting to a tertiary care hospital

Abstract: Objective: To assess the frequency of symptoms and impact on quality of life in individuals with dry eye disease. Methods: The cross-sectional, study was conducted from December 2018 to June 2019 at the outpatient clinic of the Department of Ophthalmology, Pakistan Institute of Medical Sciences, Islamabad, Pakistan, and comprised dry eye disease patients aged at least 13 years with ocular burning sensation, lacrimation, grittiness, photophobia, redness or itching. Tear Film Breakup time <10 sec and / or pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In this study, the most common ocular symptoms were a burning sensation, redness of eyes, watery eyes and foreign body sensation (eye grittiness and scratchiness). Burning sensation of the eye was also reported among 33% and 32% in a study conducted in Karachi [15] and India [11], respectively. Another study reported relatively less prevalence of burning sensation as experienced by participants [23].…”
Section: Declarations Fundingmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study, the most common ocular symptoms were a burning sensation, redness of eyes, watery eyes and foreign body sensation (eye grittiness and scratchiness). Burning sensation of the eye was also reported among 33% and 32% in a study conducted in Karachi [15] and India [11], respectively. Another study reported relatively less prevalence of burning sensation as experienced by participants [23].…”
Section: Declarations Fundingmentioning
confidence: 75%
“…In different population-based studies, the prevalence of DED among computer users has been estimated to vary from 25-75% [7]. A study in Pakistan evaluated dry eye syndrome and associated risk factors among computer users and found the prevalence of dry eye to be 28% [15]. A prevalence of 44.3% was also reported on symptomatic dry eye and its associated factors, and non-contact lens computer operators found that 68% of men and 73% of women reported dry eye symptoms [16].…”
Section: Discussionmentioning
confidence: 99%
“…7 DED is a common ophthalmologic disease that causes unbearable burning and foreign body sensations in the eye and is easily affected by bright light. [8][9][10] Under normal conditions, the ocular surface (cornea, conjunctiva, lid, and paracrine glands), nerves, and the main lacrimal gland are involved in regulating tear secretion and tear film formation, and problems with any of them can cause DED. 11,12 The prevalence of dry eye gradually increases in dry environments, air pollution, and long-term eye work.…”
Section: Introductionmentioning
confidence: 99%
“…In an American survey (2020), respondents with dry eye disease had greater problems with mobility, self-care, daily activities, pain/discomfort, and anxiety/depression, compared with respondents without dry eye disease 8 . Multiple studies have shown that this can negatively affect the quality of life 1,9,10 …”
mentioning
confidence: 99%
“…8 Multiple studies have shown that this can negatively affect the quality of life. 1,9,10 Recent literature also seems to indicate that there is a strong correlation between dry eye disease and psychological complaints. [11][12][13] A 2017 systematic review including participants with dry eye disease, glaucoma, age-related macular degeneration, and cataract found the highest prevalence of depression (29%) in the dry eye disease group.…”
mentioning
confidence: 99%